If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 9) + -7(x + -9) = 11(x + -2) Reorder the terms: 5(9 + x) + -7(x + -9) = 11(x + -2) (9 * 5 + x * 5) + -7(x + -9) = 11(x + -2) (45 + 5x) + -7(x + -9) = 11(x + -2) Reorder the terms: 45 + 5x + -7(-9 + x) = 11(x + -2) 45 + 5x + (-9 * -7 + x * -7) = 11(x + -2) 45 + 5x + (63 + -7x) = 11(x + -2) Reorder the terms: 45 + 63 + 5x + -7x = 11(x + -2) Combine like terms: 45 + 63 = 108 108 + 5x + -7x = 11(x + -2) Combine like terms: 5x + -7x = -2x 108 + -2x = 11(x + -2) Reorder the terms: 108 + -2x = 11(-2 + x) 108 + -2x = (-2 * 11 + x * 11) 108 + -2x = (-22 + 11x) Solving 108 + -2x = -22 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. 108 + -2x + -11x = -22 + 11x + -11x Combine like terms: -2x + -11x = -13x 108 + -13x = -22 + 11x + -11x Combine like terms: 11x + -11x = 0 108 + -13x = -22 + 0 108 + -13x = -22 Add '-108' to each side of the equation. 108 + -108 + -13x = -22 + -108 Combine like terms: 108 + -108 = 0 0 + -13x = -22 + -108 -13x = -22 + -108 Combine like terms: -22 + -108 = -130 -13x = -130 Divide each side by '-13'. x = 10 Simplifying x = 10
| 5(3n+3)=7(9n+5)+2 | | 0.4t+3(1.2+0.9)=21.1 | | 6x+1+1=7x+1 | | 7(8cx+y)=55cx-2y | | -4.9x^2+18.9x+2.8=0 | | 2x-15+6=x | | 11+4x-2=8x-3 | | -2Y-6=-2Y-9 | | x^2-65=0 | | x+15+2x+11=14 | | 20*x+2*y=z | | 33z+7z^2=10 | | 3(6+c)=2(c-2) | | -2|7-3y|-6=-14 | | x+15+2x+6=14 | | 2x^4-5x^2+2=0 | | 7x^2-2x-8=0 | | -20+2x+12=4+x | | x+7+2x+6=13 | | 5m+29m+(-15m)= | | 3x^3+5x^2=27x+45 | | 2x-1+3x=14 | | x(x+2)(5x-1)=0 | | 4(4k+2)-8(k-1)=3(2k+3)-2 | | x-4=5-6x | | 6a+7+11=0 | | 3(2x-1)+3(x)=6(3) | | x-5+2x=-5+9x | | -7c+2=-33 | | 5+(5x+2)=9x-1 | | 28-12=4(x-7) | | 2x-3=-6x+4 |